Implementation of Progressive Leadership at Muhammadiyah 1 High School Klaten - Kusuma, Muhamad Halim; Prayitno, Harun Joko; Sumardjoko, Bambang; Yuliani, Fatimah (Jurnal Sains Sosio Humaniora, 2025)
The key to successful school management and development is the principal. Principals must have a progressive type of leadership in managing and developing their schools. Principals must be able to think smart so as to bring up various creativity and innovation in school development. The objectives of the study are (1) to describe the implementation of progressive leadership of school principals in SMA Muhammadiyah 1 Klaten; (2) to describe the challenges faced; (3) to describe problem solving solutions. The approach used is a qualitative approach with a case study design. Data were taken from informants, namely teachers and employees who have worked for at least five (5) years at SMA Muhammadiyah 1 Klaten so that they know the Principal well. Data analysis techniques include data reduction, data presentation and conclusion drawing. The results of the research are: (1) The implementation of progressive leadership in school activities, including the preparation of school activity plans and budgets, the preparation of school programs, the selection of Vice Principals, IT-based training, Continuous Professional Development (PKB), the formation of school-level Committees, and the use of e-report cards, school websites, and social media; (2) The challenges are resistance to change, limited resources, pressure from a crowded curriculum and administrative demands, and lack of staff and teacher competence; (3) Efforts to overcome challenges through various strategies include an inclusive approach, utilization of existing resources, improved communication, and competency development.